Skeletal Injuries and Their Pattern Following Mountaineering and Climbing Accidents in Iranian Athletes - Faeze Abbasi; Haleh Dadgostar; Mahrokhsadat Vaziri; Sara Lotfian (Acta Medica Iranica, 2023)
The number of mountaineers and climbers has increased over the last few years. Considering the geographical features of Iran, this increase in the number of climbers is more significant in this country. Because of the importance of mountaineering injuries, a comprehensive survey of these injuries is needed. In this base, we designed a survey to investigate skeletal injuries in mountaineering accidents. This cross-sectional study was conducted on athletes from the Mountaineering Federation of Islamic Republic of the Iran (MFIRI) in 2015 and 2016. A total of 110 athletes were included using a simple random sampling method, and they were examined for any complications after skeletal injuries. Their medical records were reviewed. A total of 110 mountaineers completed the checklists, and 15 mountaineers reported a rock-climbing trauma and injury during 2015 and 2016. The most traumatic location was the lower extremities (46.7%). Additionally, most of trauma occurrences were in descent (80%) and times of day between noon and midnight (64.3%). The mean age of the mountaineers who had a trauma incidence was 37.95±8.76 years. Smoking was significantly different between the two groups. Skeletal injuries during mountaineering and rock climbing mostly affect the lower extremities, followed by the upper extremities and spine. There was no significant difference in age, sex or climbing equipment between the group who had an accident and the group who did not. In this study, there was a relationship between smoking cigarettes and an increased incidence of climbing accidents. Longitudinal studies with larger sample sizes are needed to evaluate this relationship.